Strategies of Legitimisation and Delegitimisation in Selected American Presidential Speeches - Trajkova, Zorica; Neshkovska, Silvana (Respectus Philologicus, 2019)
[full article and abstract in English] Politicians invest a lot of time and effort to win elections and present themselves in the best possible manner. They use language strategies to present and legitimise themselves as the right choice. And if they are the right choice, then their opponent is obviously not, so while they are trying to acclaim themselves and their political party, they use strategies to delegitimise and attack their opponents and the policy they represent. This paper aims to conduct a critical discourse analysis of the speeches of the two main political opponents in the last elections in the USA, Donald Trump and Hillary Clinton. The research gives an insight into the manipulative function of language and covers two aspects: the lexical-semantic and pragmatic aspect and is based on the supposition that the strategies politicians use while talking about themselves and describing their opponents differ. As expected, they use more positive terminology to talk about themselves and their policies, and negative terminology to criticise the opponent’s policy. They also employ different pragmatic strategies, such as intensifiers and inclusive pronouns, to involve the audience into the discourse and convince them in their arguments. Finally, although carried out on a relatively small corpus, the analysis gives an insight into the language techniques employed by politicians to legitimise themselves and delegitimise their opponent and thus win the elections.